REVIEW DESAIN PERHITUNGAN STRUKTUR PROYEK GEDUNG KANTOR SATPOL PP DI KOTA SAMARINDA - KHAIDIR, RIZAL (KURVA S JURNAL MAHASISWA, 2014)
Shop building collapse in housing Cendrawasih    Permai,  Sungai Pinang, Jalan A Yani, Samarinda Kal-team to the attention of all parties. The loss and the impact it had very detrimental to all parties, especially the workers and the project is and how much more casualties. The failure which   led    to the collapse of the construction of this building   is   concerned      suwatu   and     tarnished the city samarinda. Seventeen three-storey tenement buildings that collapsed suddenly, leavingdebris crushed material.              As a result   of this incident the need for building  design should consider several criteria, including criteria   for the power construction, efficient time and cost, power, wind  load, seismic   calculations, and also other aspects. Multistory building plan in terms of structure requires  careful   consideration,    particularly building up structural work very useable and implemented standards in the world, especially in the field of civil engineering building.              In the implementation of this final project  with   Design     Review to be conducted projected Sick Building Office in the city of Samarinda. Up     Design Review for comparison of the structure calculations so that the     calculations are reviewed planner and will look different because planners 3 floors and converted into 5 floors. Adaiah calculation method of building structures  with   SAP   2000 program, Manual calculation using the standard  Takabeya. Calculation   SNI 03-2847-2002 until this calculation